Single-molecule detection of coumarin-120 - Brand, L; Eggeling, C; Seidel, C (1997)
Two-photon excitation with a mode-locked titanium: sapphire laser at 700 nm and confocal fluorescence microscopy have been used to detect single Coumarin-120 (C-120) molecules. The dye C-120 is quenched by the nucleobases, if coupled to nucleotides, resuiting in nucleobase-specific fluorescence lifetimes. This suggests applications in current projects for ultrasensitive DNA characterization.